Worker assignment in dual resource constrained assembly job shops with worker heterogeneity: an assessment by simulation. Issue 20 (17th October 2020) - Thürer, Matthias; Zhang, Haiwen; Stevenson, Mark; Costa, Federica; Ma, Lin
Abstract : Most shops in practice are constrained by more than one resource. Consequently, a large body of literature on dual resource constrained shops has emerged. This research typically focuses on worker assignment rules, with attention being on when and where to move workers. In contrast, the decision concerning who to reallocate to a station has received limited attention. The limited prior work assumes workers are assigned to a new station as soon as they become available or seeks to minimise the risk of worker idleness. Using simulation, we question this assumption and show that it can be beneficial to introduce additional worker idleness to ensure workers only work at their most efficient station(s). In general, it is less likely that there are several workers available for one station than it is for there to be multiple stations available for one worker. Consequently, the Who Rule is used less frequently than the Where rule and has less of an impact on performance. Finally, considering the criticality of work orders as part of the Where Rule is important in assembly shops; but if labour is heterogeneous then the focus should be on efficiency. The findings have important implications for research and practice.